Living on the street: sociodemographic, economic, and motivational aspects - Márcia Astrês Fernandes; João Gabriel Ribeiro dos Santos; Ana Paula Cardoso Costa; Sandra Cristina Pillon (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To assess sociodemographic and economic aspects and motivations for living on the streets. Methods: A cross-sectional study of 127 homeless people in the city of Teresina, Piauí, Brazil. Data were collected in person between October 2019 and March 2020. A descriptive analysis of the results obtained was performed. Results: The sociodemographic profile observed was that of male, single, brown, with children, with a low level of education and income. The main reasons for homelessness were family conflicts, use of psychoactive substances and unemployment. Conclusion: The phenomenon of homelessness is perceived as a broad and complex process influenced by biopsychosocial events that occur throughout the life cycle, which requires a holistic approach by health professionals towards people in this situation.